Optimalisasi Peranan Artificial Intelligence dalam Membangun Moderasi Beragama di Universitas Islam Kadiri - Sumadiyah, Siti; Syarifah, Syarifah; Nurhasanah, Muwahidah (JOM, 2025)
This study explores the role of Artificial Intelligence (AI) in promoting religious moderation at the Islamic University of Kadiri (UNISKA) Kediri. The application of AI in religious education enhances the learning experience by offering personalized, interactive, and multimedia-based content that aligns with the values of moderation, tolerance, and interfaith dialogue. AI-powered learning platforms allow for the customization of materials according to students’ individual needs, facilitating their understanding of the significance of religious moderation. Despite its potential, the implementation of AI faces challenges, such as disparities in digital access, resistance to technological change, and ethical concerns related to privacy and data security. Nevertheless, AI presents opportunities to improve educational accessibility, personalize learning experiences, and foster interfaith dialogue. By integrating AI into religious education, UNISKA Kediri has the potential to create a more inclusive and tolerant academic environment. Strategic planning, collaboration among lecturers, AI experts, and religious leaders, alongside ongoing training, are essential for the successful implementation of AI at UNISKA Kediri.